Estruturas de governança na agroindústria canavieira paranaense: uma análise sob a ótica da Nova Economia Institucional - Tomé, Luiz Henrique Paloschi (2015)
Given the complex economic relations between the agents that comprise the Agribusiness Systems (SAG's) and the historical importance of national sugarcane sector, as well as the representation of Paraná State in the sector, the objective of this research was to analyze the factors influencing the choice of governance structures in the sugarcane agroindustry in Paraná. Thus, we analyzed from the perspective of New Institutional Economics (NIE) and Transaction Cost Economics (TCE), the characteristics of transactions, agents and organizational and institutional environments in which they operate the processing of sugarcane agro industries object of study. The research was qualitative, since it aimed to increase knowledge about transactions and the specific governance structures of each agribusiness, and to identify the factors that influence the contractual forms adopted. It was applied one multi case study in two called Paraná sugarcane agro industries Alfa and Beta. Data collection occurred through interviews and electronic correspondence with representatives of agro industries and the State of Paraná Bioenergy Producers Association (ALCOPAR), bibliographical research and document analysis. The results showed that the effects of institutional changes and the organizational environment on the choices of agro industries were the same for both agro industries, as expected since the analyzed companies are part of the same market, economic sector, institutional and organizational environments, and are located in the same state. It was observed that the changes in the institutional environment directly affected the ways to transact and the strategic positioning of companies, in addition, were also confirmed actions to change the institutional environment for agribusiness, with representatives in all spheres of government to the defense the sector's interests. It was evident that the organizational environment is well structured in SAG's sugarcane of Paraná and fundamental for raising the logistic efficiency of it. Regarding the influence of the characteristics of the transactions and the agents, uncertainty and bounded rationality were the most relevant factors in the choice of governance structures by Alfa, Beta was for the cooperative ideology (cooperative). Thus, the variables studied by NIE, asset specificity, frequency and uncertainty were the most shown to influence the choices of the analyzed agro industries governance structures, especially in relation to the supply of raw materials; reputation had a slight influence; and opportunism was not found. Finally, it was observed that there is empirical evidence of most theoretical points raised by the NIE to explain the choices of contractual forms.